The association of knowledge with behavior and pineapple consumption behavior in hypercholesterolemia patients at Clinic X Yogyakarta - Kusuma, Deny; Yulianto, Danang; Nanda Putri, Septiana (Borobudur Pharmacy Review, 2026)
Hypercholesterolemia is a major risk factor for cardiovascular disease. In addition to pharmacological therapy, the use of natural ingredients such as pineapple (Ananas comosus) has the potential as a supportive therapy. This study aims to analyze the relationship between knowledge levels and behavior regarding the use of pineapple as a complementary therapy in ihypercholesterolemic patient. An analytical observational study with a cross-sectional design was conducted among 100 patients at Clinic X Yogyakarta using purposive sampling. Data were collected through a validated questionnaire and analyzed using the Spearman Rank test. The results showed that most respondents had a moderate level of knowledge (84%) and a moderate level of usage behavior (68%). A significant relationship was found between the level of knowledge and usage behavior (p < 0.05; r = 0.400). It can be concluded that increasing knowledge has the potential to improve the behavior of pineapple use as a complementary therapy for hypercholesterolemia.